Heterogeneity as heterodoxy in development policy Tribal communities in Bangladesh and Kerala - Farida Chowdhury Khan (International Journal of Development Issues, 2013)
Purpose – A fundamental premise of economic theory is that of a homogenous subject. This unified and intentional subject also implicitly defines the welfare function that forms the foundation of economic development theory and policy today. Unfortunately, such a concept of agency is representative of mostly urban and majority populations and does not include indigenous communities who are peripheral in most developing nations. The concept of development presumes an attachment to modernization and deracination, paying little heed to conservation of natural resources that are of sacral value to tribal communities. This paper aims to show how economics neglects cultural and group differences and yet asserts a powerful influence on development policy. Institutional economists and anthropologists have contested this hegemony but at the same time have also been co-opted into development management in several ways that are discussed below. Design/methodology/approach – The case of indigenous communities in Bangladesh is investigated and their exclusion from development elucidated by citing the conflicts that tribal groups have had with majority populations and the state. This is compared to the situation of tribal communities in the state of Kerala in India. Findings – It is concluded that a heterogeneous imaginary at the level of the nation state allows possibilities for indigenous voices to be represented in development policy formation and that such heterogeneity itself opens the channel for an alternative construction of development. Research limitations/implications – The case studies may not be widely applicable to every context. Practical implications – The universality of policy suggestions should be questioned if such policy is not representative of minorities within the context of a nation. Originality/value – The point that methodological individualism and the grounding in economics of development theory leads it to avoid community concerns has not been addressed before. The paper also looks at a historical development of the discourse of development in a new way. Finally, the case of Bangladesh has not been discussed in this manner or compared to Kerala.